Association between deficient levels of vitamin D and the occurrence of selected retinal diseases - Żmijewska, Aleksandra; Maleszewska, Monika; Sztybór, Mateusz; Nowak, Gabriela; Kapica, Marcin; Piątkiewicz, Julia; Krzyżanowska, Maria; Momot, Karol; Wojtas, Mikołaj; Głogowska, Karen (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Vision originates in the eye’s retina, a complex structure essential for processing visual information. The connection between nutritional inadequacy, particularly vitamin deficiencies, and overall health, including ocular health, has long been acknowledged. Recent studies highlight the potential impact of vitamin D, a crucial nutrient, on retinal health. The aim is to investigate the association between low levels of vitamin D and retinal diseases like age-related macular degeneration (AMD) and diabetic retinopathy (DR), and to evaluate the potential benefits of vitamin D supplementation or lifestyle changes for at-risk patients. Description of the State of Knowledge: AMD, a significant cause of blindness in the elderly, involves factors like oxidative stress and inflammation. Various stages of AMD require different treatments, with limited options for advanced stages. DR, a complication of diabetes, leads to conditions such as retinal ischemia and neovascularization. Both conditions are potentially influenced by vitamin D levels. Studies show mixed results regarding the impact of vitamin D on these diseases. Some suggest lower levels may increase risk, while others report no significant effect or even contradictory findings. Conclusions: While some studies indicate a potential association between low vitamin D levels and the occurrence of retinal diseases, discrepancies exist in the findings. Lower vitamin D concentrations may be linked to a higher frequency of AMD and DR, but the evidence is not consistent across all studies. Therefore, a more in-depth exploration of this subject is warranted to draw conclusive insights. It is crucial to consider supplementation or dietary changes in cases of vitamin D deficiency, given its potential impact on systemic health.